Perineal skin tear repair following vaginal birth; skin adhesive versus conventional suture – a randomised controlled trial. (17th February 2021) - Dasrilsyah, Rima Anggrena; Kalok, Aida; Ng, Beng Kwang; Ali, Anizah; Teik Chew, Kah; Lim, Pei Shan
Abstract: This was a prospective randomised controlled trial comparing the effects of first-degree perineal tear repair using adhesive glue versus conventional suturing in terms of pain score, wound complication and patient's satisfaction. One hundred and twenty one women were randomised. The skin adhesive group had a significantly lower pain score at rest as well as during sitting, walking and micturition during the first week of delivery compared to the suture group. The time taken to become pain free was significantly shorter in the tissue adhesive group (3.18 vs. 8.65 days, p < .001). Only two patients who had skin glue experienced wound gaping. No significant difference was observed in the level of satisfaction between the adhesive and suture groups. Tissue adhesive is better than subcuticular suture for repairing first-degree perineal tear as it causes less pain and has shorter recovery time. Impact statement: What is already known on this subject . First- and second-degree tears following vaginal delivery are common and involved a third of women. Suturing of these tears is advocated to avoid wound gaping and poor healing. What the results of this study add. For first-degree tear repair, tissue adhesive is better than conventional suture in terms of pain reduction and recovery time. What the implications are of these findings for clinical practice and/or further research . Skin adhesive is an ideal method for first-degree perineal tear repair especially in out of hospital settings such as home birth or midwifery-led centre. A larger scale study is needed to establish its feasibility for second- and third-degree tears repair.